2013
DOI: 10.1097/sla.0b013e3182a6191d
|View full text |Cite
|
Sign up to set email alerts
|

Residual Esophageal Cancer after Neoadjuvant Chemoradiotherapy Frequently Involves the Mucosa and Submucosa

Abstract: After nCRT for esophageal cancer, both the mucosa and the submucosa show frequent residual malignant involvement. The surrounding stroma and the regional lymph nodes show the highest percentage of pCR and the overall regression pattern is most frequently a mixed pattern of both concentric regression and regression toward the lumen. This overall regression pattern lends support to careful testing of a wait-and-see approach in a subgroup of patients with esophageal cancer after nCRT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
52
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(55 citation statements)
references
References 45 publications
(47 reference statements)
3
52
0
Order By: Relevance
“…At times, when a clinical complete response is achieved, there is the temptation on the part of the patient, and sometime physicians, to delay/avoid surgery. However, based on our results and those of others, 9 it is clear that EAC is a highly resistant cancer and 70% of the time, residual cancer is found. Our data also contradict the conclusions made by Shapiro et al that we can implement wait and see approach in some trimodality-eligible patients.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…At times, when a clinical complete response is achieved, there is the temptation on the part of the patient, and sometime physicians, to delay/avoid surgery. However, based on our results and those of others, 9 it is clear that EAC is a highly resistant cancer and 70% of the time, residual cancer is found. Our data also contradict the conclusions made by Shapiro et al that we can implement wait and see approach in some trimodality-eligible patients.…”
Section: Discussionsupporting
confidence: 76%
“…Shapiro et al reported one noteworthy effort 9 in which 102 consecutive patients with EC (squamous and adenocarcinoma both and they included cases that did not have any residual cancer in the specimen) were analyzed for geographic distribution of EC after chemoradiation. Only 74 patients had EAC (it is not clear how many of these had resistant EAC).…”
Section: Introductionmentioning
confidence: 99%
“…Shapiro and Joel et al observed that after NACRT, residual oesophageal cancer frequently involves mucosa and submucosa, whereas surrounding stroma and regional lymph nodes had highest pathological complete response. This regression pattern supports a wait and see approach after NACRT 13. A study by Oppedijk et al 14 revealed that NACRT followed by surgery significantly reduced haematogenous dissemination and locoregional recurrence when compared to surgery alone.…”
Section: Discussionmentioning
confidence: 78%
“…For the assessment of the pathological tumor and node downstaging, the initial tumor area, before nCRT, was estimated based on the extent of regressional changes (eg, fibrosis, keratin pearls, mucous lakes, and/or foreign body cell reactions) and on the residual tumor cells in the resection specimen, as has been described previously. 30,31 These measurements were expressed as prepT and prepN, reflecting the assumed original depth of the primary tumor and the assumed number of originally involved lymph nodes, respectively. PrepT and prepN were compared with the eventual pathological ypT and ypN stages in the resection specimen after nCRT.…”
Section: Assessment Of Treatment Responsementioning
confidence: 99%